1998
DOI: 10.1128/aac.42.8.2036
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Arrests Growth of Intracellular Toxoplasma gondii

Abstract: Addition of paclitaxel (Taxol) at a concentration of 1 μM toToxoplasma gondii-infected human foreskin fibroblasts arrested parasite multiplication. Division of theT. gondii tachyzoite nucleus was inhibited, leading to syncytium-like parasite structures within the fibroblasts by 24 h after infection and treatment of the cultures. By 4 days after infection and treatment of the cultures with paclitaxel, this inhibition was irreversible, since the arrested intracellular form was incapable of leaving the host cell,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…At the maximum tolerated and recommended Phase II doses for PTX administered as a 6-h infusion, plasma levels have approached 10 M for 2-4 h, and have exceeded 1 M for 24 h, and 0.1 M for 48 h (Rowinsky et al, 1988). Besides, PTX did not alter the growth of fibroblasts at a concentration of 8.54 g/ml (Estes et al, 1998).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…At the maximum tolerated and recommended Phase II doses for PTX administered as a 6-h infusion, plasma levels have approached 10 M for 2-4 h, and have exceeded 1 M for 24 h, and 0.1 M for 48 h (Rowinsky et al, 1988). Besides, PTX did not alter the growth of fibroblasts at a concentration of 8.54 g/ml (Estes et al, 1998).…”
Section: Discussionmentioning
confidence: 84%
“…PTX has antineoplastic properties and is used to treat certain human malignancies (Rowinsky and Donerhower, 1995;Huizing et al, 1995). In vitro studies have shown that PTX inhibits the growth of the apicomplexan parasites P. falciparum and Toxoplasma gondii (Pouvelle et al, 1994;Estes et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] In addition to cancer, the microtubular cytoskeleton has been implicated in the etiology of a wide variety of diseases including neurodegenerative and mental diseases, [13][14][15] viral infections, [16][17][18] and parasitic diseases. [19][20][21][22][23][24] Therefore, pharmaceuticals that target microtubules may have wide clinical applications. Moreover, compounds targeting the microtubular cytoskeleton have proven to be valuable tools for basic research in cell biology.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have demonstrated that clarithromycin has synergistic activity with pyrimethamine in the effective treatment of toxoplasmosis [33]. Other drugs showing activity against Toxoplasma include atovaquone, artemisin, paclitaxel, trovafloxacin and quinupristin-dalfopristin [34][35][36][37][38][39].…”
Section: Therapymentioning
confidence: 98%